The Effect of Product-Harm Crises on the Financial Value of Firms under the Concept of Green Development. (12th March 2021) - Li, Songsong; Yang, Yaopan; Zhang, Dong
Abstract : Product-harm crises can trigger product recalls or product discards, which is very likely to cause secondary pollution to the environment. Also, these crises may harm customers' health and threaten firms' survival. To foster low-carbon economy and green development in such complex systems, this paper studies the internal mechanism of the product crisis and its impact on the firm value. It proposes a two-stage model to avoid the endogeneity of product-harm crises. In the first stage, this paper assesses the effect of firms' leverage on their capacity to produce higher quality products. In the second stage, this paper conducts the impact of these crises on stock prices. Then, it depicts the financial effects of product-harm crises over time, and analyzes the differences of such effects based on brand equity. Results show that book leverage can positively impact firms' capacity to produce high-quality products. In addition, the market's response to product-harm crises is significant at 1% level, and with the increase in severity, the market reaction is more prominent. Furthermore, its negative effect is persistent for a firm experiencing a severe crisis. Luckily, brand equity can mitigate this negative impact. These findings provide some ways to improve product performance and firm value in the green context.